2017
DOI: 10.1103/physrevd.95.094014
|View full text |Cite
|
Sign up to set email alerts
|

Z(3) metastable states in a Polyakov quark meson model

Abstract: We study the existence of Z(3) metastable states in the presence of the dynamical quarks within the ambit of Polyakov quark meson (PQM) model. Within the parameters of the model, it is seen that for temperatures Tm greater than the chiral transition temperature Tc, Z(3) metastable states exist ( Tm ∼ 310 MeV at zero chemical potential). At finite chemical potential Tm is larger than the same at vanishing chemical potential. We also observe a shift of (∼ 5• ) in the phase of the metastable vacua at zero chemica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…This interpretation allows for very interesting possibilities for the QGP phase with rich phenomenology which can have very important implications for cosmology. This finds support in the recent lattice calculations of QCD with quarks [20] and also in the effective model studies of QGP [21] which suggest that there is a strong possibility of existence of these Z(3) vacua at high temperature.…”
Section: Introductionsupporting
confidence: 69%
“…This interpretation allows for very interesting possibilities for the QGP phase with rich phenomenology which can have very important implications for cosmology. This finds support in the recent lattice calculations of QCD with quarks [20] and also in the effective model studies of QGP [21] which suggest that there is a strong possibility of existence of these Z(3) vacua at high temperature.…”
Section: Introductionsupporting
confidence: 69%
“…Since the fermions break the Z N symmetry, we expect that finite μ will lead to more explicit breaking. Following Roessner et al, for small μ, we calculated the thermodynamic potential to the leading order, i.e., keeping only the real terms and found that T m increases slightly with μ [29]. With increase in T m there is lesser time available for the nucleation of bubbles, which enhances the likelihood of metastable states becoming unstable.…”
Section: Introductionmentioning
confidence: 96%
“…In general, nonperturbative lattice simulations are essential for a quantitative estimate of the explicit symmetry breaking; however, the mean field approaches provide a qualitative understanding. In a recent study of Z 3 symmetry in the Polyakov loop quark meson model [29], it is found that the metastable states exist above 310 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…Bananas are widely grown in large plantations in tropical and subtropical countries and approximately 106.54 million tons of banana fruits are produced every year, which contributes to 16% of total food production in the world . Cultivation of banana generates a large amount of byproducts, which includes pseudostems, leaves, peduncle, and those ungraded bananas that do not meet the high‐quality standards.…”
Section: Introductionmentioning
confidence: 99%